Installation and Testing of Electric Generators in Civil Engineering Structures for Microhydro Power Plants in Nagari Kamang Hilia Agam - Risma Apdeni; Nevy Sandra; Fitra Rifwan; Prima Zola; Elisa Mayenti (Universitas Negeri Padang, 2025)
This community service program, conducted by Universitas Negeri Padang in Nagari Kamang Hilia, Agam Regency, focused on the planning, construction, and utilization of a micro-hydro power plant to support local agricultural activities. The program began with coordination with the Nagari government and community to identify challenges and beneficiaries, followed by technical surveys including water discharge mapping, hydraulic head measurement, and land suitability analysis using GIS and UAV-based mapping. Based on these data, detailed engineering designs were prepared for the turbulence-based intake structure, inlet channel, and powerhouse. The project then advanced to the construction of civil works, the installation of turbines, generators, and control panels, and the testing of the operational system. With an installed capacity of up to 5 kW, the plant now provides renewable electricity for agricultural use and street lighting, helping reduce dependence on costly diesel engines. Training and counseling were also delivered to ensure that the community can operate and maintain the system independently. The program demonstrates how micro-hydro technology can be effectively applied to foster rural electrification, empower local farmers, and contribute to sustainable development goals.